How managers' risk perceptions affect their willingness to blame advisors as scapegoats. Issue 4 (August 2022) - Aschauer, Florian; Sohn, Matthias; Hirsch, Bernhard
Abstract: Managers spend considerable amounts of corporate money to hire consultants. The research proposes two potential benefits of consultants' advice: increasing decision accuracy and sharing responsibility with the advisor. In contrast to previous research, which has predominantly focused on factors influencing decisional accuracy, this paper evaluates the sharing of responsibility in the form of using an advisor as a scapegoat. We conduct an online experiment with 175 managers from German-speaking countries in an investment setting. We find that the presence of a potential scapegoat positively affects advice utilization in an economic boom but negatively affects such utilization in an economic crisis due to managers' varying risk perceptions. Managers' risk perceptions are the main drivers of scapegoating as a form of managerial blame avoiding decision-making. We contribute to management research and highlight managers' opportunistic motives behind consulting (costly) advice. Highlights: Managers use advisors as scapegoats in order to avoid blame. This effect is more pronounced in an economic boom than in an economic crisis. The more risk managers perceive, the more pronounced this effect. The higher the advice utilization, the less own responsibility managers perceive. Risky investments are perceived as less risky when recommended by a scapegoat.